Economic Empowerment Of Ummah Through Sharia Fintech:Literature Review (International Journal of Scientific Research and Management (IJSRM), 2023)
Fintech Syariah is an innovation that has the potential to strengthen the Islamic economy by providing more inclusive and syariah-compliant access to financial services. This article provides comprehensive literature on how Islamic finance technology benefits Muslim economies. Using a variety of literary analyses, this article explains how Fintech Syariah may increase access to money, provide innovative solutions for social and economic problems, and reduce the risk associated with financial inception. We also outline the necessary regulatory measures that must be taken to ensure that Islamic economic principles are adhered to in Fintech. The current study provides insight into how Fintech Syariah may become a significant tool for Muslim economic development, with implications that are particularly significant for the growth of the Islamic economy in the current digital era.